JUSTICE, EMPLOYEE VOICE AND ANTAGONISTIC BEHAVIORS IN ORGANIZATIONS - Kutaladze, Iamze; Tsulaia , Nino (Georgian Psychological Journal, 2022)
The study aims to assess the role of organizational justice in the formation of antagonistic, deviant behavior through the analysis of indirect relationships and via new (previously unexplored) conﬁguration of organizational and individual characteristics. We have introduced the agreeableness and job satisfaction variables to describe indirect relationships. The article presents a comparative analysis of the impact of organizational justice on positive and antagonistic behaviors.Employee voice moderates the relationship between organizational justice and antagonistic behavior. Increased perception of fairness of the organization is associated with a more active choice of proactive, constructive voice by employees, whereas unfair environment increases the probability of silence. On the other hand, employee voice, manifested in the expression of personal opinions and ideas reduces the probability of the manifestation of antagonistic behaviors. The interaction variable of organizational justice and agreeableness enhances the expression of voice, which signiﬁcantly reduces antagonistic behaviors, and, at the same time, contributes to the formation of positive organizational behaviors. Employee voice moderates the relationship between organizational justice and job satisfaction. When employees choose silence strategy instead of voice strategy, even a fair organizational environment cannot compensate this ‘loss’ (restriction of voice), which results in dissatisfaction with job. The study was conducted in Georgia in 2020. 839 employees participated in the study.